Cytokinesis: Cytoskeleton and Chromosome Damage Leading to Abnormal Mitosis Were Involved in Multinucleated Cells Induced by Silicon Nanoparticles (Part. Part. Syst. Charact. 6/2015). (June 2015) - Li, Yang; Jing, Li; Yu, Yongbo; Yu, Yang; Duan, Junchao; Yang, Man; Geng, Weijia; Jiang, Lizhen; Li, Qiuling; Sun, Zhiwei
<x xml:space="preserve">Abstract</x> Silicon nanoparticles are capable of inducing oxidative damage of the cell cytoskeleton and DNA, leading to abnormal mitosis and cytokinesis. As shown by Z. Sun and co‐workers on page 638, this ultimately results in the formation of multinucleated cells in the L‐02 cell line.